2021
DOI: 10.1093/ndt/gfab344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-angiotensin II type 1 receptor antibodies on the outcomes of kidney transplantation: a systematic review and meta-analysis

Abstract: Background Anti-angiotensin II type 1 receptor antibodies (AT1R-Abs) have been recognized as non-HLA antibodies associated with allograft rejection and poor allograft outcomes after kidney transplantation. The aim of this study was to assess the risk anti-AT1R-Abs pose for rejection and graft loss among kidney transplant populations. Methods We systematically searched PubMed, EMBASE, and the Cochrane Library databases for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Clinical studies examining the association between AT1R-Ab and clinical outcomes have been highlighted in a recent review 32 and meta-analysis. 8 Most studies have focused on pretransplant AT1R-Ab and short-term allograft outcomes. Interestingly, one adult study found that patients with high pretransplant AT1R-Ab had a higher risk of rejection in the first 4 mo posttransplant, but a higher risk of allograft loss only after 3 y posttransplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies examining the association between AT1R-Ab and clinical outcomes have been highlighted in a recent review 32 and meta-analysis. 8 Most studies have focused on pretransplant AT1R-Ab and short-term allograft outcomes. Interestingly, one adult study found that patients with high pretransplant AT1R-Ab had a higher risk of rejection in the first 4 mo posttransplant, but a higher risk of allograft loss only after 3 y posttransplant.…”
Section: Discussionmentioning
confidence: 99%
“…AT1R-Ab and ETAR-Ab have been associated with AMR, vascular pathology, increased cytokines, and allograft dysfunction in KTRs. [3][4][5][6][7][8][9][10] The mechanisms of injury remain unclear; both classical mechanisms of antibody-mediated allograft injury and overactivation of G protein-coupled receptors may contribute to the clinical findings. 3,11,12 We and others [13][14][15][16] have recently reported the increased prevalence of AT1R-Ab and ETAR-Ab in pediatric KTRs.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, positive cutoffs associated with adverse outcomes range from 9 to 17 U/mL. 14 Based on our receiver operating characteristic curve analysis and the known association between younger age and high AT1R-Ab levels, we generally use >17 U/mL as a positive cutoff for our pediatric kidney transplant recipients. 17 However, in different contexts, levels as low as 9.5 U/mL may be relevant.…”
Section: At1r-ab Te S Tingmentioning
confidence: 99%
“…17,22 A recent meta-analysis provides a full table of studies in adults and pediatric patients on this topic with annotation of studies looking at pre-and post-transplant AT1R-Abs. 14 Despite the availability of these studies, the question of how to treat patients with a positive pre-transplant test is a controversial one.…”
Section: At1r-ab In Pre-tr An S Pl Ant Patientsmentioning
confidence: 99%
“…While the number of publications linking non-HLA antibodies to the development of ABMR histology (ABMR h ) is growing, it is still unclear how these non-HLA antibodies contribute to kidney allograft damage and graft failure. Currently, there is inadequate consensus for routine testing of any non-HLA antibody for diagnosing ABMR (8)(9)(10)(11)(12), although there is growing literature on the role of anti-angiotensin receptor II type 1 antibodies as risk factor for ABMR and graft failure and for potential future clinical implementation (13,14).…”
Section: Introductionmentioning
confidence: 99%